Micellization behavior of bile salt with pluronic (F‐127) and synthesis of silver nanoparticles in a mixed system. (21st May 2019) - Rub, Malik Abdul; Azum, Naved; Asiri, Abdullah M.; Khan, Anish; Alamry, Khalid A.; Kosa, Samia A.; Nazeeruddin, Mohammad Khaja
Abstract: The sequestrant is a substance used to cure bile salt diarrhea. They bind to bile salts by hydrophobic and electrostatic forces to stop them from contact with colon mucosa. The block copolymer could be used as bile salt binding agents. Herein, the physicochemical parameters between bile salt and block copolymer have been studied for a new potential sequestrant. The mixed micellization behavior of bile salt, sodium deoxycholic acid (NaDC) with pluronic (F‐127) was investigated by the tensiometry method. Various micellar and thermodynamic parameters were computed. The results of the present study have been analyzed by using different theoretical models for mixed binary systems. The obtained data indicate attractive interactions (synergistic interactions) among two components upon mixing. Silver nanoparticles (AgNPs) were synthesized by using a chemical reduction method. We used single and mixed amphiphilic solution in different compositions for stabilizing silver nanoparticles. The resulting silver sol was analyzed using UV‐visible spectroscopy and scanning electron microscope (SEM). Abstract : Herein, the physicochemical parameters between bile salt (sodium deoxycholic acid (NaDC)) and block copolymer (pluronic (F‐127)) have been studied for a new potential sequestrant. Various micellar and thermodynamic parameters were computed. The obtained data indicate attractive interactions (synergistic interactions) among two components upon mixing. Silver nanoparticles (AgNPs) were synthesized using a chemical reduction method. The resulting silver sol was analyzed using UV‐visible spectroscopy and scanning electron microscope (SEM).